Formation of Complex Value of Enterprise Based on Digital Marketing: The Theoretical Aspects - Kononov Oleksandr I. (Bìznes Inform, 2022)
The purpose of the article is a theoretical substantiation of the process of forming the complex value of an enterprise based on digital marketing in the current conditions of economic management. According to the results of the carried out study, it was found that it is necessary to generalize the approaches to defining the essence of the value category that exist in various international standards, compare them with the interpretation of value in accordance with domestic standards, and on this basis lay the foundations for determining the complex value of the enterprise, which takes into account generally accepted concepts and reflects the domestic features of the formation of enterprise value based on digital marketing under market development conditions. In this article, it is proposed to define the complex value of the enterprise as an estimated value equal to the amount of money formed taking into account marketing factors, the value of the enterprise by tangible assets and the potential of the intellectual marketing capital of the enterprise. The conception of forming the complex value of an enterprise based on digital marketing involves the selection of key value factors. After all, digital marketing is not an alternative to «traditional», but new opportunities that allow to achieve impressive results. And the combination of factors and their gauges, transformed into a marketing function, is called the intellectual marketing capital of the enterprise. It is proposed to include the following ones to the marketing factors for the formation of the complex value of the enterprise: brand and trust in it; reputation as a result of the application of digital marketing; marketing information system that uses the capabilities of Big Data; marketing strategy based on the use of digital marketing tools; customer loyalty based on trusting relationships. Thus, the study considers the conception of forming the complex value of an enterprise based on digital marketing and provides a scheme for its formation, which involves the selection of key value factors.